Global Shutter and Charge Binning With Quantum Dots Photodiode Arrays for NIR Imaging - Loic Baudoin; Arthur Arnaud; Sebastien Massenot; Pierre Magnan (IEEE Journal of the Electron Devices Society)
New applications like depth measurements or multispectral imaging require to develop image sensors able to sense efficiently in the Near Infrared and Short-Wave Infrared where silicon is weakly sensitive. Colloidal Quantum Dots (CQD) technology is an interesting candidate to address these new applications as it allows to develop image sensors with high quantum efficiency at excitonic peak and high-resolution images. In this paper, we present an electrical model describing the electrical behavior of a designed and manufactured CQD photodiode. We use this model to explore a different architecture collecting holes instead of electrons. This architecture allows to control the charge collection inside the CQD thin film through the electric field. This property enables to implement global shutter functionality, to bin charges from several photodiodes, or to operate two physically interleaved photodiodes arrays alternatively with different types of pixel circuitries. These operating modes extend the capabilities of CQD image sensors in terms of applications.